Naa12 compensates for Naa10 in mice in the amino-terminal acetylation pathway - Kweon, Hyae Yon; Lee, Mi-Ni; Dorfel, Max; Seo, Seungwoon; Gottlieb, Leah; PaPazyan, Thomas; McTiernan, Nina; Ree, Rasmus; Bolton, David; Garcia, Andrew; Flory, Michael; Crain, Jonathan; et al. (ELIFE SCIENCES PUBLICATIONS LTD, 2021)
Amino-terminal acetylation is catalyzed by a set of N-terminal acetyltransferases (NATs). The NatA complex (including X-linked Naa10 and Naa15) is the major acetyltransferase, with 40-50% of all mammalian proteins being potential substrates. However, the overall role of amino-terminal acetylation on a whole-organism level is poorly understood, particularly in mammals. Male mice lacking Naa10 show no globally apparent in vivo amino-terminal acetylation impairment and do not exhibit complete embryonic lethality. Rather Naa10 nulls display increased neonatal lethality, and the majority of surviving undersized mutants exhibit a combination of hydrocephaly, cardiac defects, homeotic anterior transformation, piebaldism, and urogenital anomalies. Naa12 is a previously unannotated Naa10-like paralog with NAT activity that genetically compensates for Naa10. Mice deficient for Naa12 have no apparent phenotype, whereas mice deficient for Naa10 and Naa12 display embryonic lethality. The discovery of Naa12 adds to the currently known machinery involved in amino-terminal acetylation in mice.
Keywords: N-ALPHA-ACETYLTRANSFERASE; CARDIAC NEURAL CREST; CERVICAL-VERTEBRAE; PROTEIN; PAX3; MOUSE; GENE; IDENTIFICATION; MUTANT; ARD1